Interlinked credit, relational contracting, and the spread of rural-based manufacturing the case of garment and metalcraft industries in the Philippines - Briones, Roehlano M. (2002)
Subcontracting arrangements based on relational contracting between urban traders and rural-based manufacturers provide an important means for spreading manufacturing in rural areas. Within these arrangements, the payment of advances is a form of credit interlinking that addresses the isolation of rural-based enterprises from the formal finance sector. This viewpoint motivates specification of a testable hypothesis: advance payments are greater the more remote a rural-based subcontractor is from the urban center. The paper shows that such a hypothesis can be derived from a simple principal-agent model of the subcontracting relation. Moreover, the hypothesis is empirically confirmed by multivariate analysis of data from a case study of garment and metalcraft industries in the Philippines. The finding supports the view that subcontracting arrangements may be an organizational form appropriate to rural industrialization.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 120).
Keywords: Credit -- Philippines; Rural credit -- Philippines